Character Education of Prof. Dr. KH. Asep Saefuddin Chalim, MA (Analysis of the Poems in the Book of Dhalilun Najah) - Ulumuddin, Ihya; Ma’arif, Muhammad Anas (Anjasmoro: Islamic Interdisciplinary Journal, 2024)
Education is the key to civilization, where instilling good character values ​​ will strengthen the character foundations of the nation's children. From this literary work, the authors want to convey a meaning contained in it. Dhalilun Najah's book Clue to success of Prof. Dr. KH. Asep Saefuddin Chalim, MA. The book is a book published in 2018 which will be researched and reviewed in the contents of the book. What kind of clues to success do you offer? Prof. Dr. KH. Asep Saefuddin Chalim, MA so that you can achieve a dream and can form character. This research aims to the poems in Dhalilun Najah related to the character values ​​contained in Prof. Dr. KH. Asep Saefuddin Chalim, MA., and analyze Prof.'s character education learning model. Dr. KH. Asep Saefuddin Chalim, MA in the poetry of Dhalilun Najah. By using the type of literature review research (Library Research). The approach used in this study is qualitative. The data source in this research is the book Dhalilun Najah by Prof. Dr. KH. Asep Saefuddin Chalim, MA chapter on poetry pages 57 to 66. The results of the research that have been examined by the author are 1) the character values ​​contained in the poems of Dhalilun Najah by Prof. Dr. KH. Asep Saefuddin Chalim, MA, among others: a) Religious, b) Tolerance, c) Discipline, d) Hard work, e) Independence, f) Love of Peace, g) Love of Reading, h) Responsibility, these eight characters are contained in Dhalilun Najah's poetry which is the basis for character education in the book by Prof. Dr. KH. Asep Saefuddin Chalim, MA. 2) The character education learning model in the poetry of Dhalilun Najah by Prof. Dr. KH. Asep Saefuddin Chalim, MA uses an information processing model which this model has four components, namely: a) approach, b) learning strategy, c) method, d) learning technique.